Uncertainty Reduction of First-Year College Students in Virtual Class - Sofia Aunul; Fitrie Handayani; Riswandi Riswandi (Universitas Ahmad Dahlan, 2022)
Many college students are now adjusting to the virtual environment, some as they start their studies for the first time. With this significant shift, students may feel anxious or uncertain about not having sufficient information about their classmates and lecturers. It may be a big problem for new students as their level of uncertainty may increase. It is their first experience of having a virtual class without face-to-face interaction before the semester starts. This study aimed to determine the delay in communication experienced by college students and their strategies to reduce this uncertainty. The theories and concepts used in this study are the theory of uncertainty reduction and the concept of virtual classes. This study uses a descriptive qualitative approach that uses interviews with ten students from six universities as the primary data. The results showed that informants experienced uncertainty in virtual lectures, and they used active, passive, and interactive strategies to reduce this uncertainty.